Next century mathematics : precalculus : grade 11 : senior high school - Orines, Fernando B. (Quezon City : Phoenix Publishing House, Inc., 2016)
"The textbook is designed to provide both the teachers and the learners an instructional material that will cover the 80-hour semester course. Specifically, through this book, the learners are expected to model situations appropriately and solve problems using conic sections and systems of nonlinear equations: keenly observe and investigate patterns, and formulate appropriate mathematical statements and prove them using mathematical induction and/or Binomial Theorem; formulate and solve accurately situational problems involving circular functions; apply appropriately trigonometric identities in solving situational problems; formulate and solve situational problems involving appropriate trigonometric functions; and formulate and solve accurately situational problems involving the polar coordinate system Each unit starts with the learning competencies derived from Steven Covey's principle of beginning things with the end in mind. Each topic is thoroughly discussed with provision for variety of relevant examples and easy-to-follow solutions. Sufficient set of exercises are provided. These are categorized into MathSelfie which is designed for individual enhancement, MathGroupie which is designed for cooperative learning, and MathSmash which is designed to challenge the inquisitive minds of the learners."
English text.
Keywords: Precalculus